Preparation and Properties of Sludge and Coal Gangue Composite Polymer - Xu, Zifang; Zou, Xiaotong; Yang, Zheng (Asian Journal of Chemistry, 2014)
In view of a larger number of wastewater treatment sludge and coal-product of waste rock disposal problems of environmental resource, studied the scientific preparation of the both things into new gelling geological polymer. Let 40 % sludge (< 5 μm) after roasted at 900 ºC for 45 min displace gangue to make the geopolymer has good compressive strength. XRD and SEM analyze the preparation of the novel geopolymer mechanism. The result shows that the effective composition such as CaO, MgO and SiO2 of thermally activated sludge and the alkaline substances K2O and Na2O provided the alkaline environment to the polymerization reaction, Conducive the depolymerization of gangue aluminosilicate phase and the dissolution and diffusion of the depolymerized aluminosilicate complexes, accelerated the polymerization reaction. The results of this study enriched the selection of raw materials of geopolymers, helped the resource utilization of industrial wastes such as the sludge and waste rock containing the aluminosilicate phase.